Changes in foliage projective cover and its implications for mapping groundwater dependent vegetation across a precipitation gradient. Issue 4 (12th January 2018) - Parker, Brett M.; Sheldon, Fran; Phinn, Stuart; Ward, Doug
Abstract: Adequate protection of groundwater dependent vegetation (GDV) at the landscape scale (>10 4 km 2 ) is often hampered as their extent is poorly mapped. Remote sensing data sets have previously been used to delineate GDV by analysing both actual and changes, in green biomass over space and time. The rationale behind such approaches is based on the phenological characteristics of GDV, which often retain greater mean green biomass during dry periods, in comparison to vegetation with access to soil moisture only. However, such methods are hampered by inadequate knowledge about how average annual precipitation, seasonality, and differing water regimes of vegetation communities within a landscape influence green biomass. Therefore, we aimed to test for amount of foliage projective cover (FPC) and variation in FPC as indicators of GDV presence. We assessed differences in the FPC of GDV at 3 sites across a 1, 500 mm −1 year −1 precipitation gradient, ranging from arid inland to humid coastal environments in Southern Queensland, Australia. Overall, we found that average annual precipitation had the largest influence on predicting FPC followed by seasonality. During winter in the semi‐arid and humid environments (season with least precipitation), FPC for non‐GDV was higher than subsurface GDV. For our study area, GDV delineation on the basis of higher green biomass than surrounding vegetation was effective when average annual precipitation was less than 600 mm −1 year −1 .